In Vitro Ovine Embryo Culture: Effectiveness of TCM-199 in Combination with 17?-Estradiol Hormone and Co-Culture of FTEC - Ondho, Yon Soepri; Lestari, Dela Ayu; Samsudewa, Daud (Jurnal Veteriner, 2020)
Objective of this research was to determine the effectiveness of various culture mediums on the cleavage to morula in in vitro embryo culture of ovine. A total of 1.064 zygotes (fertilized oocytes) were grown in three kinds of different embryo culture medium, which were Tissue Culture Medium 199 (TCM-199) (T1), TCM-199 + 17â-estradiol (T2) and TCM-199 + co-culture of Fallopian Tube Epithelial Cell (FTEC) (T3). Data were analyzed using a completely randomized design with ANOVA analysis and Honestly Significant Difference test. The variable observed were the percentage of embryo cleavage and morula. Results showed that T3 had the highest percentage (72.45%) of the cleavage occurred in zygotes cultured in the TCM-199 + FTEC co-culture medium, as well as embryo growth to the morula stage (75.75%). In contrast, zygotes cultured in T1 and T2 had lower cleavage and lower morula development than T3, as much as 27.38%; 47.82% and 58.15%; 66.66%, respectively. In conclusion, TCM-199 + FTEC co-culture medium is the best medium for embryo culture.